Evaluation of oral tradition-based reading instruction on secondary students reading competence - Teófilo Félix Valentín Melgarejo; Clodoaldo Ramos Pando; Pablo Lolo Valentín Melgarejo; Fidel Alberto García Yale; William Cesar Santos Hinostroza; Rober Wesmel Sánchez Trinidad; Ulises Espinoza Apolinario; Rosa Luz Gómez Segura; Tito Armando Rivera Espinoza; José Rovino Alvarez López; Julio César Carhuaricra Meza; Flaviano Armando Zenteno Ruiz (International Journal of Evaluation and Research in Education (IJERE), 2026)
Reading competence is a developmental and multidimensional construct that is often evaluated through mean score comparisons that may obscure structural learning changes. This study examined the effectiveness of a culturally grounded oral tradition–based intervention on primary students’ reading competence in Pasco, Peru. A quantitative quasi-experimental pretest–posttest design with a control group was implemented using intact classrooms (experimental n=19; control n=14; N=33). The eight-week intervention integrated local myths, legends, and folktales into guided reading, inferential questioning, and evaluative discussion activities. Reading competence was assessed using narrative texts scored with an analytic rubric classifying students into four ordered achievement levels (initial, in process, expected, and outstanding). Data were analyzed using ordinal mobility analysis, distributional dominance testing, and dynamic-systems indicators. Results showed complete structural stability in the control group, whereas 89.5% of students in the experimental group demonstrated upward mobility and all reached expected or outstanding levels at posttest. These findings indicate that culturally responsive oral-tradition instruction can produce substantial structural improvements in reading competence. This study contributes to educational evaluation by demonstrating how ordinal mobility and dynamic-systems indicators reveal instructional effects that may remain hidden in traditional mean-based analyses.